Pengaruh Pengaruh Konsentrasi Polivinil Alkohol dan Lama Pengadukan pada Proses Pemanasan Terhadap Karakteristik Komposit Biotermoplastik Maizena dan Glukomanan - Limbong, Sando F.; Harsojuwono, Bambang Admadi; Hartiati, Amna (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2022)
This study aims to determine the effect of the concentration of polyvinyl alcohol (PVA) and the stirring time on the heating process and their interactions on the characteristics of the cornstarch-glucomannan biothermoplastic composite and determine the concentration of polyvinyl alcohol (PVA) and the duration of stirring the heating process which produces the best biothermoplastic composite. This study used a factorial randomized experimental group design. The first factor is the concentration of polyvinyl alcohol which consists of 4 levels, namely 3,5%, 4%, 4,5%, and 5% (w/w). The second factor is the stirring time on the heating process which consists of 4 levels, namely 3, 4, 5, and 6 minutes. The variables observed in this study were tensile strength, elongation at break, elasticity, swelling, water vapor transmission rate, biodegradation, and functional group. The resulting data was analyzed and continued with Duncan's Multiple Range Test. The results showed that the concentration of polyvinyl alcohol (PVA) had a very significant effect on tensile strength, elongation at break, and elasticity, but had no significant effect on swelling, water vapor transmission rate, and biodegradation. While the stirring time on the heating process has a very significant effect on tensile strength, and elasticity, but has no significant effect on elongation at break, swelling, water vapor transmission rate, and biodegradation of biothermoplastic maizena-glucomannan. The interaction between treatments has no significant effect on the characteristics of biothermoplastic. The best biothermoplastic composites were composites with a polyvinyl alcohol concentration of 5% and a stirring time of 6 minutes with a tensile strength of 29,47 MPa, elongation at break of 10,99%, elasticity of 268,21 MPa, swelling of 65,02%, water vapor transmission rate of 1,05 g/m2.hour, and biodegradation rate for 6 days. The results of functional group analysis showed the presence of functional groups hydroxyl (O-H), carbonyl (C=O), C=C aromatic, carboxyl (C-O), and hydrocarbon -(CH2)n.